A fraude contra a ordem tributária como elemento autorizador da apreensão de mercadorias e interdição de estabelecimentos - Sousa, Geraldo Marcelo (2024)
Tax fraud causes enormous losses to the public treasury and free competition. The intention of taking undue advantage by violating the tax system, especially through the irregular circulation of goods and the irregular use of commercial establishments, are very common forms of fraud. The intention of the study is to analyze whether the unequivocal finding of fraud against the tax system can be an authorizing element for the tax authorities to adopt exceptional coercive measures to seize goods and close establishments. In a context of need to apply urgent measures, which aim to immediately cease and prevent the continuation of serious conduct contrary to the tax order, we delve into reflections on the legal support that the tax authorities have at their disposal, or would need to have, to act to guarantee the interests of the state. The study seeks to expose situations in which fraud often occurs in the movement of goods and in the irregular use of establishments formally registered, or not, in the tax registers. In this context, it analyzes some norms of our legal system and the STF's position on the matter. Highlights legal circumstances that limit or prevent the potential exercise of tax authorities' powers to combat fraud by seizing goods and closing establishments. On the other hand, it highlights situations in which the police power attributed to the state, linked to other branches of law, allows the exercise of these same extreme coercive measures, in case of non-compliance with the rules to which it refers. In this effort, we intend to demonstrate the need for very clear legislation that governs this matter, starting from an express constitutional authorization to the provision in a complementary law of the general aspects in order to regulate the circumstances for the exercise of such powers. At the end of the analysis, the aim is to obtain a clearer horizon on the need for this type of intervention and the possibilities of its application, in addition to a better vision of its suitability for the current constitutional system.